Open access networks and national broadband plans: Tales from down - Fernando Beltrán (International Telecommunications Society (ITS), 2012)
Recently, governments in many countries have acknowledged the higher complexity involved in finding the more efficient path towards a so-called broadband ecosystem. The governments of Australia and New Zealand are leading the deployment of national fibre-based broadband infrastructures through Public-Private-Partnerships (PPP). The paper is on the approach followed by New Zealand and Australia to developing Next-Generation broadband infrastructure, their broadband policies and strategies for network deployment. It also contributes an economic analysis that allows understanding the economics of those country-wide broadband platforms.The paper critically analyses the short history of each experience, including the political process, the reasons exhibited that justify the governments' involvement in infrastructure deployment, and the institutional arrangements introduced to manage the PPP. The paper's main goal is to contribute analytical tools to the understanding of the economic effects of a purpose-made infrastructure on the markets that, according to every government's declared expectation, will be propelled by the combined effect of policy decisions, regulations and technology deployment. The paper analyses the effect of network design principles such as open access and regulated wholesale tariffs on the efficiency of service markets to be deployed on the fibre-based next-generation platform.
Keywords: 330